Effects of L1 Dominance on the Acquisition of English Sounds by Turkish/Persian Bilinguals - Afshar Naeimeh (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. This study will investigate the process of acquiring the sound structure of English by bilingual Turkish-Persian speakers in the south-west of Iran, more specifically addressing the question whether bilinguals will do better than monolinguals in pronouncing the sounds of English. The samples will be selected from 30 Turkish bilinguals as well as from 30 Persian monolinguals. Participants are high-school students learning English as a foreign language. There will be two experimental groups and two control groups in order to compare and analyze the data. The sound structure of three languages, i.e. Turkish, Persian and English, will be studied to discover structural similarities and differences between the native and the foreign languages. Also the participants’ familiarity with producing and perceiving the native and foreign sounds will be tested to see (i) if there is dominance of one native language over the other, and (ii) whether the dominance is reflected in the pronunciation and/or perception of the English sounds. Finally, the participants’ language attitude towards the native and foreign languages will be determined and related to the acquisition process. In order to meet the time frame, the study will be confined to the perceptual representation of only the vowel phonemes. As a first approximation, English texts with target words full of vowel sounds will be prepared plus a background questionnaire, which covers issues such as the participants’ age, gender, L1, bilinguality status, age of acquisition of the language(s) they speak, degree of using each language daily, and so forth

Резюме. У цьому дослідженні вивчено процес отримання звукової структури англійської мови двомовними турецько-перськими ораторами на південному заході Ірану. Конкретна мета аналізу – чи будуть двомовні особу вимовляти краще, ніж монолінгви, звуки англійської мови. Зразки будуть відібрані з 30 турецьких білінгвалів, а також з 30 перських одномовних осіб. Учасники – учні середньої школи, які вивчають англійську мову як іноземну. Для порівняння та аналізу даних будуть дві експериментальні групи та дві контрольні групи. Буде вивчено звукову структуру трьох мов, тобто турецької, перської та англійської, щоб виявити структурні подібності та відмінності між рідною та іноземною мовами. Також буде перевірено знайомство учасників з вимовою і сприйняттям рідних і іноземних звуків. Нарешті, мовне ставлення учасників до рідних та іноземних мов буде визначено та пов'язане з процесом оволодіння. Для того, щоб задовольнити часові рамки, дослідження буде обмежено перцептивним поданням тільки голосних фонем. У першому наближенні будуть підготовлені англійські тексти з цільовими словами, наповненими голосними звуками, а також анкета, яка охоплює такі питання, як вік учасників, стать, L1, статус двомовності, термін вивчення мови, на якій вони говорять, ступінь використання кожної мови щодня і так далі.

A kutatás az Irán délnyugati részén élő kétnyelvű török–perzsa beszélőknek az angol hangrendszer elsajátításának sajátosságait vizsgálja. Konkrétabban azzal a kérdéssel foglalkozik, hogy a kétnyelvűek jobban elsajátítják-e az angol hangok kiejtését, mint az egynyelvű beszélők. A kutatási mintát 30 török kétnyelvű és 30 perzsa egynyelvű adatközlő közül alakítjuk ki. A résztvevők középiskolások, akik idegen nyelvként tanulják az angolt. Az adatok összehasonlítása és elemzésére céljából két kísérleti csoportot és két kontrollcsoportot hozunk létre. A kutatás résztvevői tanulmányozzák a három nyelv (török, perzsa és angol) hangrendszerét, hogy felfedezzék az anyanyelv és az idegen nyelvek közötti szerkezeti hasonlóságokat és különbségeket. Az időkeretek miatt a kutatás csak a magánhangzó fonémák észlelésére korlátozódik. Első lépésben meghallgatják az angol nyelvű szövegeket, amelyekben a szavak tele vannak magánhangzókkal, valamint kitöltenek egy háttér-kérdőívet, amely olyan kérdésekre terjed ki, mint például a résztvevők életkora, neme, első nyelve (L1), kétnyelvűségi szintje, a nyelv(ek) elsajátításának kora, az egyes nyelvek napi használatának mértéke stb.
A domináns első nyelv (L1) hatásai az angol nyelv hangzóinak elsajátítására török/perzsa kétnyelvű személyek körében
Впливи домінантної першої мови (L1) на засвоєння звучання англійської мови у середовищі двомовних турецько-перських осіб
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008905
Keywords: English vowels; Acquisition of English Sounds; Turkish-Persian Bilinguals; south-west of Iran; high-school students